Unveiling the Social Media Revolution in Tourism: Unraveling Instagram's Profound Influence on Travelers - Utama Dewayani, Eka Kadharpa; Nahar, Faiza Husnayeni; Nugroho, Tyo (Advances in Tourism Studies, 2023)
This research explores the profound impact of social media on tourist behavior, focusing on destination selection and decision-making. Utilizing a mixed-methods approach, including surveys, interviews, and content analysis, the study provides comprehensive insights into this phenomenon. The findings reveal that social media platforms significantly influence tourists' destination choices by offering user-generated content and peer recommendations. Real-time updates, interactive content, and virtual conversations enable informed decision-making and diverse travel experiences. Moreover, social media facilitates the discovery of hidden gems and fosters engagement with local communities, enhancing overall tourism experiences. The study emphasizes the importance of effective social media utilization by destination marketers and policymakers to engage with tourists and shape their choices. Understanding social media's impact on tourist behavior informs strategies for destination marketing, visitor engagement, and sustainable tourism development.